The impact of pre-patterns on the design of digital home applications - Saponas, Scott; Prabaker, Madhu; Abowd, Gregory; Landay, James A. (Proceedings of the 6th ACM Conference on Designing interactive Systems, 2006)
Recent research suggests design pre-patterns, structured collections of evidence-based research and design knowledge, provide a useful resource for design activities in emerging application domains. This paper extends previous research by exploring the impact of pre-patterns and tools to support pre-pattern exploration for the domain of ubiquitous computing in the home. We conducted an empirical study of 44 designers engaged in a two hour concentrated brainstorming and design task for the home of the future. Our results show pre-patterns are an easily adopted resource for designers that can impact even the earliest of design activities. We also provide insights for future development of pre-patterns based on designer feedback.